ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PERUSAHAAN PERIODE 2015-2017 - Marcelina Rosario, Merry Susanti (Jurnal Paradigma Akuntansi, 2020)
This research aims to obtain empirical evidence about the effect of audit committee, board size, independent commissioner, firm size, institutional ownership, andintellectual capital on firm performance. This research uses secondary data obtained from the site www.idx.co.id. The population of this research is manufacturing companies listed in the Indonesia Stock Exchange (IDX) during the year 2015-2017. This research is conducted with a sample of 64 manufacturing companies out of 140 manufacturing companies as the population. The data in this research is processed by Eviews version 10.0. The results of this research show that audit committee and intellectual capital has positive effect on firm performance, while board size, independent commissioner, firm size andinstitutional ownership has no effect on firm performance.